Perancangan Sistem Informasi Serba Usaha pada Koperasi Tangerang - Karmawan, I Gusti Made (Bina Nusantara University, 2014)
Savings and loan cooperative or credit and trade unions is part of a Multipurpose Cooperative Enterprises engaged in the field of small - medium businesses. Capitalization is achieved through the savings of its members in a way that is easy, inexpensive, fast, and accurate for the purpose of productivity and prosperity for the members. This study was conducted to design information systems, computer-based savings and loan in order to help improve performance. The purpose of information system design in Tangerang savings and loan cooperatives are providing computerized system of savings and loan and trading. The methodology used in the design of information systems is developing a System Life Cycle (SDLC). The results of this study indicate that the use of information systems Savings and Loans, Trade, and Services can provide solutions to the activities undertaken in terms of speed, precision and accuracy in carrying out data processing activities of savings and loan in order to get optimal results.